Effective advertising appeals for websites of small boutique hotels - Lwin, Michael; Phau, Ian (Emerald Group Publishing Limited, 2013)
Purpose: The purpose of this paper is to investigate whether rational and emotional appeals are more effective for small boutique hotel websites in Australia. Specifically, it assesses how attitudes towards websites, service expectations and attitudes towards boutique hotels will influence purchase intention under the two different types of appeals. Design/methodology/approach: Using a systematic intercept approach, a total of 249 useable data was collected in a large suburb of Western Australia. Results were analysed using t-test and a series of multiple regressions. Findings: The results show boutique hotel websites that used emotional appeals performed differently to those that used rational appeals. Further analysis shows that emotional appeals evoked more favourable attitudes towards the website and attitudes towards the boutique hotel. In addition, websites that utilised emotional appeals were a stronger predictor of purchase intention. Research limitations/implication: The research focuses only on homepages of the boutique hotels. Further, the study was limited to two rational (price and service accolades) and two emotional appeals (warmth and serenity). Originality/value: The study is the first to provide empirical evidence on the effectiveness of website appeals. It broadens the scope of the service communication literature by exploring rational and emotional appeals in an interactive medium.